The art and science of Military Deception - Rothstein, Hy; Whaley, Barton (Artech House intelligence and information operations series, 2013)
This book is a comprehensive collection of classic articles on deception, hand-picked and expertly introduced by well-known experts on military deception. The purpose of this book is to set in motion a renaissance for using deception as an instrument of statecraft. The various sections are designed to cumulatively provide sufficient breadth and depth on the subject to satisfy both the novice as well as the expert.